Saturated vs. unsaturated hydrocarbon interactions with carbon nanostructures - Umadevi, Deivasigamani; Sastry, G. Narahari (Frontiers in Chemistry, 2014)
The interactions of various acyclic and cyclic hydrocarbons in both saturated and unsaturated forms with the carbon nanostructures (CNSs) have been explored by using density functional theory (DFT) calculations. Model systems representing armchair and zigzag carbon nanotubes (CNTs) and graphene have been considered to investigate the effect of chirality and curvature of the CNSs towards these interactions. Results of this study reveal contrasting binding nature of the acyclic and cyclic hydrocarbons towards CNSs. While the saturated molecules show stronger binding affinity in acyclic hydrocarbons; the unsaturated molecules exhibit higher binding affinity in cyclic hydrocarbons. In addition, acyclic hydrocarbons exhibit stronger binding affinity towards the CNSs when compared to their corresponding cyclic counterparts. The computed results excellently corroborate the experimental observations. The interaction of hydrocarbons with graphene is more favourable when compared with CNTs. Bader’s theory of atoms in molecules has been invoked to characterize the noncovalent interactions of saturated and unsaturated hydrocarbons. Our results are expected to provide useful insights towards the development of rational strategies for designing complexes with desired noncovalent interaction involving CNSs.